Beneficial effects of curcumin and capsaicin on cyclophosphamide-induced premature ovarian failure in a rat model - Rauf Melekoglu; Osman Ciftci; Sevil Eraslan; Asli Cetin; Nese Basak (Journal of Ovarian Research, 2018)
Abstract Background In recent years, cancer rates have been rising among reproductive-age women. Thus, chemotherapy exposure has become an important cause of premature ovarian failure (POF). There has been growing interest regarding the preservation and restoration of ovarian function before and after oncological treatment because of the reproductive risk of chemotherapeutics and improved long-term survival of cancer patients. In this study, we sought to analyze the effects of curcumin (CRC) and capsaicin (CPS) on cyclophosphamide-induced POF in a rat model. Methods POF in rats was induced by intraperitoneal injection of 200 mg/kg cyclophosphamide on day 1 and then 8 mg/kg/day for the following 14 days. After 14 days of cyclophosphamide administration, rats were randomly divided into three groups as follows (n = 10/group): POF, POF + CRC (100 mg/kg/day), and POF + CPS (0.5 mg/kg/day) to determine the effects of CRC and CPS on the cyclophosphamide-induced POF rat model. Biochemical, hormonal, and histopathological evaluations were performed on blood and tissue samples 14 days after the CRC and CPS treatments. Results Malonaldehyde levels were significantly reduced, and glutathione levels and superoxide dismutase activity were significantly increased, in ovarian tissues in the POF + CRC and POF + CPS groups compared with the POF group. In the POF group, we observed hemorrhage and prominent mononuclear cell infiltration beneath the germinative epithelium, vascular congestion in ovarian stroma, hemorrhage around the corpus luteum, and atresia in ovarian follicles. This histopathological damage was significantly improved by treatment with CRC and CPS. There was a significant reduction in serum follicle-stimulating hormone and luteinizing hormone levels in rats treated with CRC and CPS compared with the POF group. Moreover, the levels of estradiol and anti-mullerian hormone in rats treated with CRC and CPS were significantly increased compared with the control group. Conclusions In conclusion, CRC and CPS treatment of rats with cyclophosphamide-induced POF had a beneficial effect on reducing ovarian damage by improving tissue oxidative stress marker levels, ovarian reserve marker levels, and histopathological parameters. The significant improvements in ovarian tissue histopathological damage and hormonal levels detected in this study indicate that treatment with CRC or CPS might be a conservative treatment approach for cyclophosphamide-induced POF.